2005
DOI: 10.1159/000086751
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Myosin Heavy Chain I, IIa and IIx in Canine Skeletal Muscles by an Electrophoretic and Immunoblotting Study

Abstract: To determine which myosin heavy chain (MHC) isoforms are expressed in canine skeletal muscles, different muscle samples of five mixed-breed dogs were analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). The separated MHC isoforms were identified by immunoblotting technique using a set of specific monoclonal antibodies. To compare the results of the electrophoretic and immunoblotting study, the pattern of MHC isoform expression and histochemical profiles of canine fibres were addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 64 publications
3
36
0
Order By: Relevance
“…Western blotting and immunohistochemistry using previously validated antibodies (for both isoform specificity and species reactivity) showed that the black wildebeest expressed only MHC IIa, MHC IIx and MHC I (corresponding to the migratory pattern observed in Fig.1A) (Smerdu et al, 2005;Acevedo and Rivero, 2006;Kohn et al, 2011). This migratory profile is consistent with that from a number of large domestic and wild species, including cattle, horses, lions, dogs, tigers and cheetahs, whereas human MHC IIx migrates slower than its MHC IIa isoform (Toniolo et al, 2005;Acevedo and Rivero, 2006;Kohn et al, 2007a;Rivero et al, 2007;Hyatt et al, 2010).…”
Section: Mhc Iix Isoform Identificationsupporting
confidence: 74%
“…Western blotting and immunohistochemistry using previously validated antibodies (for both isoform specificity and species reactivity) showed that the black wildebeest expressed only MHC IIa, MHC IIx and MHC I (corresponding to the migratory pattern observed in Fig.1A) (Smerdu et al, 2005;Acevedo and Rivero, 2006;Kohn et al, 2011). This migratory profile is consistent with that from a number of large domestic and wild species, including cattle, horses, lions, dogs, tigers and cheetahs, whereas human MHC IIx migrates slower than its MHC IIa isoform (Toniolo et al, 2005;Acevedo and Rivero, 2006;Kohn et al, 2007a;Rivero et al, 2007;Hyatt et al, 2010).…”
Section: Mhc Iix Isoform Identificationsupporting
confidence: 74%
“…Both recognized slow or Type-I fibers. As these antibodies revealed Type-I fibers in skeletal muscles of different species (Rivero et al, 1996(Rivero et al, , 1999Argü ello et al, 2001;Lefaucheur et al, 2002;Š trbenc et al, 2004;Smerdu et al, 2005), it is clear that slow MHC-I isoform is highly conserved among species. On the contrary, fast MHC isoforms show species-dependent antigenic specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly slow fibres were demonstrated by BA-D5 antibody immunoreactive with /slow MyHC-I in rats (2) and humans (5) in a dilution 1:100; fast fibres were demonstrated by A4.74 antibody (former Alexis Biochemicals, now Enzo Life Sciences) immunoreactive according to the product data sheet in rats and humans with MyHC-IIA, but according to (16) with MyHC-IIA and MyHC-IIX in humans and in dogs (17). A dilution of A4.74 was 1:100.…”
Section: Methodsmentioning
confidence: 99%
“…Several distinct MyHC isoforms exist. Human limb and trunk muscles contain muscle fibres expressing skeletal muscle-specific MyHC isoform IIA (MyHC-IIA) encoded by MYH2 gene on chromosome 17, MyHC isoform IID/IIX (MyHC-IIX) (2-4) encoded by MYH1 gene on chromosome 17 and an isoform that is expressed in both skeletal and cardiac muscle MyHC-or MyHC-I encoded by MYH7 gene on chromosome 14 (5,6). Two developmental myosin heavy chain isoforms (MyHC-embryonic and MyHC-perinatal) may be present in adult muscles, particularly in regenerating muscle fibres.…”
Section: Introductionmentioning
confidence: 99%